Female sterilisations with Filshie clips: What is the risk failure? A retrospective survey of 30 000 applications. Issue 1 (1st January 2002) - Kovacs, Gabor T; Krins, Anthony J
Abstract : Objective: To assess the failure rate of Filshie clip sterilisations in Victoria, Australia. Design: Retrospective study between 1994 and 1998. Setting: All specialist gynaecologists practising in the state of Victoria, Australia. Interventions: Questionnaires (up to three) followed by telephone calls if necessary. Main outcome measures: A response rate of 276/277 (99.6%) was obtained. All pregnancies were recorded. Results: Seventy-three failures were notified from an estimated 30 000 Filshie clip sterilisations carried out in the study period. Conclusions: The estimated failure rate of Filshie clip sterilisations in the state of Victoria carried out by specialist gynaecologists was between 2 and 3 per 1000 sterilisation operations.